Tsunamigenik di Selat Sunda: Kajian terhadap katalog Tsunami Soloviev - Yudhicara Yudhicara; K. Budiono (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20086Tsunamigenic is a natural phenomena which is potential to generate a tsunami, such as water dis- turbance due to the presence of activities of volcanism, earthquakes, coastal and sub marine landslidse, or other causal factors . Historically, the Sunda Strait has experienced several tsunami events recorded in the tsunami catalog. Those tsunamies were caused by some geological phenomena such as eruptions of Krakatau submarine volcano in 416, 1883, and 1928; earthquakes in 1722, 1852, and 1958; and other causes which were suggested as a mass failure of coastal and submarine landslide in 1851, 1883, and 1889. Tectonic condition of the Sunda Strait is very complicated, because this region is located at the boundary of Indian-Australian and Eurasian Plates, where a unique island arc system occurs with its association such as trench, accretionary zone, volcanic arc and back-arc basin. Sunda trench as a plate boundary is the most potential region to produce big earthquakes. Existence of a seismic gap in the region can cause a stress accumulation and store energy, then it will be released any time as a big earthquake to generate a tsunami. Along eruption history, Krakatau volcanic arc has four stages of reconstruction and three stages of destruction, and every destruction stage produces tsunami which is suggested to be potentially repeated in the future in a period between 2500 to 2700. Seafloor of the Sunda Strait has an unstable geological condition due to geological structure development, which creates grabens and also enable to produce submarine landslides triggered by earthquake. Coastal condition around the Semangko and Lampung Bays consisting of steep topography with high intensity of weathering, is another factor to contribute landslide, particularly in the case of triggering be heavy rainfall between December to Februari. Furthermore, if landslide materials tumble into the water, even very small and locally, could create a potency of tsunami.